Association between coronary microvascular function and the vasa vasorum in patients with early coronary artery disease. (October 2016) - Park, Kyoung-Ha; Sun, Tao; Diez-Delhoyo, Felipe; Liu, Zhi; Yang, Shi-Wei; Lennon, Ryan J.; Herrmann, Joerg; Gulati, Rajiv; Rodriguez-Porcel, Martin; Lerman, Lilach O.; Lerman, Amir
Abstract: Background and aims: The vasa vasorum (VV) plays a role in the initial phase of atherosclerosis, and abnormalities in microvascular function may be sensitive measures of the early development of atherosclerosis. The current study was designed to access the association between coronary microvascular function and VV density in patients undergoing cardiac catheterization. Methods: Twenty-four patients with early coronary artery disease underwent endothelium-dependent (coronary blood flow, CBF) and endothelium-independent (coronary flow velocity reserve, CFVR) coronary microvascular function testing, and optical coherence tomography (OCT) imaging of the left anterior descending coronary artery (LAD). Using an intracoronary Doppler guidewire, CBF was examined by evaluating changes in blood flow in response to acetylcholine and CFVR in response to adenosine. VV density (VV volume/vessel volume × 100, %VV) of the proximal 10 mm of the LAD was quantified by OCT. Results: The median values (Q1, Q3) of CFVR, % changes in CBF in response to acetylcholine, and the %VV were 2.70 (2.30, 2.90),  −16.82 (−42.34, 54.52), and 2.62 (2.35, 3.35), respectively. %VV correlated inversely with CBF (r = −0.614, p  = 0.001) and directly with CFVR (r = 0.423, p  = 0.040). Multivariate analysis showed that only %VV was significantly correlated with CBF and the association was independent of other clinical variables, Framingham risk score, body mass index, and a family history of coronary heart disease. Conclusions: This study demonstrates that VV density has negative correlation with endothelium-dependent microvascular function in patients with early coronary atherosclerosis. These observations link adventitial VV structure and function to microvascular dysfunction in early coronary atherosclerosis. Graphical abstract: The study demonstrated that coronary adventitial VV density inversely correlated with myocardial endothelium-dependent microvascular function and a positive correlation with endothelium-independent microvascular function. The current study demonstrated for the first time the relationships between the coronary VV density and coronary microvascular function in humans. Highlights: Vasa vasorum density has negative correlation with endothelium-dependent microvascular function. Vasa vasorum density has positive correlation with endothelium-independent microvascular function. Our findings suggest that vasa vasorum has relevance to microvascular dysfunction in early-stage coronary atherosclerosis.